Perilaku Merokok Siswa SMP di Kecamatan Panongan Kabupaten Tangerang Tahun 2015 - Rina Khairunnisa Fadli; Anhari Achadi (UHAMKA Press, 2019)
ABSTRACT Smoking behavior at Junior High School area especially at Panongan Subdistrict has been apprehensive about enough. The study head for analyze the correlation between smoking behavior with used Lawrence Green Theory. The study used Cross Sectional Design that be supported with qualitative approach. There were 230 respondents and 6 informan to indepth interview. The result showed that smoking behavior more on boys students that have negative attitude and simple access to the cigarette, they have bad family and bad friends too. There was a significant correlation are age (p value = 0.044), sex (p value = 0.000), attitude (p value = 0.000), access (p value = 0.000), family interaction (p value = 0.006) and peer group (p value=0.000) to the smoking behavior. Meanwhile there wasn’t correlation in knowledge and school’s regulation. Access was the most important factor that influenced smoking behavior. There wasn’t specific regulation about smoking prohibition at school and there wasn’t socialization about regulation from Tangerang district to the junior high school at Panongan Subdistrict. Keywords: Cigarettes, Students, Cigarette Advertisement, School’s Regulation